Adaptation Features of Kamchatka Bilberry (Vaccinium praestans Lamb.) Plants Grown in vitro - Natal’ya R. Sungurova; Sergey S. Makarov; Anton I. Chudetsky; Yuliya S. Cheryatova (Лесной журнал)
Currently, the demand for berry products with high nutritional and medicinal value is increasing. To preserve biodiversity and industrial propagation, it is necessary to grow plants in vitro and create a gene bank. Kamchatka bilberry (Vaccinium praestans Lamb.) is one of the valuable and rare forest berry plants, which requires the improvement of accelerated propagation technologies for further cultivation. The aim of the study has been to investigate the adaptation features of in vitro propagated V. praestans plants under ex vitro conditions and in open ground. The objects of the study have been V. praestans plants (2 hybrid forms and 3 selected forms from natural populations) obtained by the in vitro method. Morphometric parameters of the regenerated plants have been taken into account under ex vitro conditions when grown on various substrates (high-moor peat; peat + river sand 3:1; peat + vermiculite 3:1; peat + perlite 3:1; peat + zeolite 3:1) treated with aqueous solutions of growth stimulants (Zircon 0.5 ml/l; Epin-extra 0.5 ml/l). When adapting ex vitro, the highest survival rates (90 %), number of shoots (3.8 pcs. on average) and number of leaves (5.1 pcs. on average) of the V. praestans regenerated plants on the 28th day after transplantation have been revealed on a substrate made of a mixture of peat and zeolite (3:1) when treated with Epin-extra 0.5 ml/l. For the first time, the morphometric parameters and yield dynamics of V. praestans plants obtained by clonal propagation have been studied in open ground conditions in the natural and climatic conditions of Moscow, the Kostroma Region and the Khabarovsk Territory. The maximum shoot length in 2022–2023 was recorded in hybrid form 235261 (7.0–7.4 cm on average). The highest yield of 2–5-year-old V. praestans plants in open ground conditions has been noted in hybrid forms (362.75–383.0 g/m2 on average) and has varied depending on the growing area.